Hepatitis C virus dynamics and cellular gene expression in uPA‐SCID chimeric mice with humanized livers during intravenous silibinin monotherapy. Issue 9 (8th June 2016) - DebRoy, S.; Hiraga, N.; Imamura, M.; Hayes, C. N.; Akamatsu, S.; Canini, L.; Perelson, A. S.; Pohl, R. T.; Persiani, S.; Uprichard, S. L.; Tateno, C.; Dahari, H.; et al.
Summary: Legalon SIL (SIL) is a chemically hydrophilized version of silibinin, an extract of milk thistle ( Silybum marianum ) seeds that has exhibited hepatoprotective and antiviral effectiveness against hepatitis C virus (HCV) in patients leading to viral clearance in combination with ribavirin. To elucidate the incompletely understood mode of action of SIL against HCV, mathematical modelling of HCV kinetics and human hepatocyte gene expression studies were performed in uPA‐SCID‐chimeric mice with humanized livers. Chronically HCV‐infected mice ( n = 15) were treated for 14 days with daily intravenous SIL at 469, 265 or 61.5 mg/kg. Serum HCV and human albumin (hAlb) were measured frequently, and liver HCV RNA was analysed at days 3 and 14. Microarray analysis of human hepatocyte gene expression was performed at days 0, 3 and 14 of treatment. While hAlb remained constant, a biphasic viral decline in serum was observed consisting of a rapid 1st phase followed by a second slower phase (or plateau with the two lower SIL dosings). SIL effectiveness in blocking viral production was similar among dosing groups (median ε = 77%). However, the rate of HCV‐infected hepatocyte decline, δ, was dose‐dependent. Intracellular HCV RNA levels correlated ( r = 0.66, P = 0.01) with serum HCV RNA. Pathway analysis revealed increased anti‐inflammatory and antiproliferative gene expression in human hepatocytes in SIL‐treated mice. The results suggest that SIL could lead to a continuous second‐phase viral decline, that is potentially viral clearance, in the absence of adaptive immune response along with increased anti‐inflammatory and antiproliferative gene expression in human hepatocytes.